Numerical study of blast-induced rock fractures under different in-situ stress and joint properties conditions. Issue 3 (October 2021) - Pan, C; Suo, Y Y; Li, X; Li, J C
Abstract: As the excavation depth of underground engineering increases, the influence of in-situ stress on the blasting effect cannot be ignored. Many joints in the natural rock mass, coupled with the initial stress, significantly affect the stress wave propagation process. Therefore, it is necessary to study the blast failure behavior of jointed rock masses under different in-situ stress conditions. In this study, a universal distinct element code-discrete fracture network model was used to examine the failure mode of jointed rock mass induced by blasting under different in-situ stress conditions. The effects of in-situ stress and joint geometric parameters on blast-induced rock fractures were analyzed systematically. The numerical results indicated that in-situ stress conditions would act against the initiation and propagation of blasting-induced cracks. The maximum cracking radius and rock breakage area decreased with increasing in-situ stress. The long joints largely prevented the propagation of cracks induced by blasting. However, as a free surface, the joint plane could increase the fracture network scope between the blasting source and joints in the process of blasting. Although it improved the crushing effect of the rock mass considerably, the effect gradually disappeared as the distance between the blasting source and joints or the in-situ stress was increased.